APLIKASI PEMELIHARAANPREVENTIVE MESIN PRODUKSI DENGAN METODE “SMART MAINTENANCE” UNTUK EFISIENSI PERUSAHAAN LUCKY OLYMPIC KEDIRI - Eko Siswanto (REVITALISASI : Jurnal Ilmu Manajemen, 2019)
Availability and reliability are still less can degrade performance (performance) of a machine, which can lead to production targets are not met. Implementation of the repair machinery for this is not trustworthy, the maintenance management system "smart maintenance." Maintenance management that emphasizes the manager of the mandate, namely: "that work is worship" that all aspects of life if the means and intention for Allah is worship, work is trustworthy which will be responsible for world until akherot..Kerugian arising from maintenance systems usually include: the majority of people working menganggab the world affairs / not worship, so lacking motivation was, and did not feel the air of responsibility to Allah. The cost of lost production, higher repair costs and overtime costs due to lost production. engine damage can occur due to internal factors (machine or component itself) or external factors (because the operator is less trust), the environment is not conducive, will be the cause not the effectiveness of maintenance and inefficient also result in unsafe and uncomfortable